UPAYA PENYELESAIAN JIKA DEBETUR WANPRESTASI DALAM PERJANJIAN KREDIT DENGAN JAMINAN FIDUSIA PADA BRI KCP UNIT PAGUYAMAN - Pantika Mayulu; Weny Almoravid Dungga; Zamroni Abdussamad (Bajang Institute, 2024)
This research aims to find out what the settlement efforts are if a debtor defaults in a credit agreement with fiduciary collateral at BRI KCP UNIT Paguyaman and what causes bad credit in terms of creditor behavior in credit agreements with fiduciary collateral at BRI KCP UNIT Paguyaman bank. This research uses empirical legal research methods and data collection techniques in this research are taken from the results of observations and interviews. The results of this research show that the creditor's out-of-court or non-litigation settlement efforts will invite the debtor to discuss the problem in order to find the best way for both the creditor and the debtor. Settlements that can be carried out include negotiation or mediation, with mutual openness from the parties, peaceful efforts will be found in resolving the credit agreement so that a civil lawsuit will not be filed in the District Court first through the normal procedural legal process until a decision is issued by the court. Factors – Factors that cause default in paying debts are health factors, economy problem, misuse of goals, and lack of good faith.